MATEMATIKA BOYÍNSHA AUDITORIYALÍQ SABAQLARDA TALABALARDÍŃ ÓZ BETINSHE JUMÍSLARÍN SHÓLKEMLESTIRIW - Jańabergenova, A. (SCIENCE and SOCIETY, 2018)
The article contains interesting ideas how to use maximally mathematical skills at lessons in the classroom and in independent work of students of higher educational institutions.